The moderating effect of general system justification on the relationship between unethical behavior and self-esteem. Issue 2 (17th February 2020) - Liang, Yuan; Liu, Li; Tan, Xuyun; Dang, Jianning; Li, Chao; Gu, Zibei
ABSTRACT: Previous studies obtained mixed results regarding the association between unethical behavior and self-esteem. To make sense of these results, the current research examined the moderating role of general system justification on the relationship between unethical behavior and self-esteem. Study 1 and Study 2, using a bribery scenario and an actual cheating behavior respectively, indicated that unethical behavior was positively related to self-esteem when general system justification was low, and the opposite was true when general system justification was high. Study 3 and Study 4, using a recall and a real behavior paradigms respectively, confirmed that the causal effect of unethical behavior on self-esteem was contingent upon general system justification. Our results imply that it is vital to increase the general system justification by promoting the process of social equity and justice to highlight the psychological cost of wrongdoing.